The One Who Whispers - The playwright as ghostwriter - Schultz, Laura Luise (Peripeti, 2017)
The plot of The One Who Whispers (2012) is simple, but in the best Shakespearean mode full of ambiguities and role play, reflections, mirages, and confusions. The tall, red-haired poet Otto, whose immense sensitivity is confusingly similar to ordinary youthful stupor, is reading an advertisement attempting to contact relatives of the deceased Jenny Holst.